Age at start of endurance training is associated with patterns of left ventricular hypertrophy in middle-aged runners. (15th September 2018) - Ryffel, Christoph P.; Eser, Prisca; Trachsel, Lukas D.; Brugger, Nicolas; Wilhelm, Matthias
Abstract: Background: Left ventricular hypertrophy (LVH) is a physiological adaptation to long-term endurance training. We investigated the impact of age at start of endurance training on LV geometry in a cohort of male, middle-aged, non-elite endurance athletes. Methods: A total of 121 healthy, normotensive, Caucasian participants of a 10-mile race were recruited and assessed with an echocardiogram and a comprehensive interview. Athletes were classified based on patterns of LVH. Results: Thirty-five athletes (31%) had LVH. Athletes with eccentric LVH (16%) were significantly younger at start of endurance training compared to athletes with concentric LVH (15%, 14 ± 5 years vs. 31 ± 8 years; P < 0.001). Although the yearly volume of endurance training was comparable between athletes with eccentric and concentric LVH, athletes with eccentric LVH had shorter race times. All athletes with an increased LV end diastolic volume index (LVEDVI; ≥74 ml/m 2 ) started endurance training before or at age 25. Conclusions: In our cohort of non-elite middle-aged runners, eccentric LVH was found only in athletes with an early start of endurance training. In case of a mature starting age, endurance training may, contrary to what is commonly assumed, also lead to concentric LVH. The consideration of endurance training starting age may lead to a better understanding of morphological adaptations of the heart. Highlights: The impact of age at start of endurance training on LV geometry was studied. Eccentric LVH was found only in athletes with an early start of endurance training. In case of a mature starting age, endurance training may lead to concentric LVH. Endurance training starting age may be crucial in cardiac morphological adaptations.